STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI EKONOMI KREATIF KAMPUNG ASIR-ASIR ASIA KECAMATAN LUT TAWAR KABUPATEN ACEH TENGAH - Faidha Rahmi; Hikmah Hikmah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
At the beginning of 2019 the world was hit by the Covid-19 pandemic which resulted in the paralysis of the economy of people around the world, including Indonesia. The government's policy to overcome this epidemic was to limit community activities (lockdown). paralyzed in all sectors. The Covid-19 pandemic has damaged the economic order of the people of Central Aceh district. Likewise, Kampung Asir-Asir Asia, one of the villages in Lut Tawar District, was also affected by the Covid-19 pandemic. Asir-Asir Asia Village is located at the foot of the Leweng hill extending along the Lut Tawar Lake. The livelihoods of the people here are mostly trading and entrepreneurship. , many of these communities are no longer able to continue their business until they really expect government assistance both from social assistance and other assistance that can lighten their burden a little. The dharma of higher education is expected to be able to provide solutions to the problems that are being faced by the Asir-Asir Asian community. This year's White Elephant University Real Work Lecture has the theme KKN-Thematic. We, from one of the field supervisors, want to strengthen the community's economy. This study aims to revive the economy of the community affected by the Covid-19 Pandemic through community empowerment in the field of creative economic production and designing business models and business plans as well as marketing expansion by utilizing degitalization so that people immediately rise from the crush of a prolonged pandemic.